What You Need to Know Before Performing Endoscopic Ultrasound-guided Hepaticogastrostomy - Tanyaporn Chantarojanasiri; Thawee Ratanachu-Ek; Nonthalee Pausawasdi (Korean Society of Gastrointestinal Endoscopy, 2021)
Endoscopic retrograde cholangiopancreatography (ERCP) is the primary treatment modality for bile duct obstruction. When ERCP is unsuccessful, percutaneous transhepatic biliary drainage can be an alternative method. Endoscopic ultrasound-guided biliary drainage (EUS-BD) has emerged as a treatment option for biliary obstruction, especially after ERCP failure. EUS-BD offers transluminal intrahepatic and extrahepatic drainage through a transgastric and transduodenal approach. EUS-guided hepaticogastrostomy (EUS-HGS) is an excellent choice for patients with hilar strictures or those with a surgically altered anatomy. The optimal steps in EUS-HGS are case selection, bile duct visualization, puncture-site selection, wire insertion and manipulation, tract dilation, and stent placement. Caution should be taken at each step to prevent complications. Dedicated devices for EUS-HGS have been developed to improve the technical success rate and reduce complications. This technical review focuses on the essential practical points at each step of EUS-HGS.